Probing the physicochemical impact of musk melon seed oil on mayonnaise - Nishat, Zahra; Yousaf Quddoos, Muhammad; Shahzadi, Neelum; Ameer, Kashif; Mohamed Ahmed, Isam A.; Yaqub, Shazia; Mukhtar, Shanza; Mahmood, Shahid; Rafique, Ayesha; Siddique Raza, Muhammad; Shahzad, Aymen; Umar Hayat, Bushra; et al. (Italian Journal of Food Science, 2024)
Owing to high consumption and industrial preparation of musk melon products, most of its byproducts are wasted without effective utilization. Musk melon agro-based waste material (seeds and peels) is an excellent source of antioxidants and phytochemicals. The purpose of this study was to improve the oxidative stability of mayonnaise by addition of musk melon seed oil. The study was conducted to check the physicochemical effect of musk melon seed oil in mayonnaise. Proximate analysis of seeds (i.e. moisture, crude fat, crude fiber, crude protein, ash, and carbohydrate content) was performed. Oil was extracted by using the cold press extraction method, and this oil was tested for different physicochemical analyses (i.e., saponification value, iodine number, specific gravity, 2,2-diphenyl-1-picrylhydrazyl [DPPH] value, viscosity, free fatty acid, and color). Physicochemical analysis was done during the storage period of 0, 20, 40, and 60 days, prior to performing sensory evaluation of mayonnaise. Data obtained from this analysis were further analyzed using statistical tools. A decreasing trend was observed for DPPH and peroxide values of mayonnaise with progression of days, thus showing that addition of musk melon seed oil decreased the production of free radicals. Hence, adding 40% musk melon seed oil showed the best result for overcoming the oxidation of mayonnaise and minimizing the production of free radicals. The data obtained from the statistical analysis indicated that the aroma and texture values of treatment T5 were maximum, and the color and flavor of treatments T4 and T5 were high. The overall acceptability of treatment T5 was high in which 40% of musk melon seed oil was used to combat the production of free radicals. In brief, waste material could be used for producing different types of products in the industry, rather than discarding the same, as it lessened the cost and provide a good quantity of nutrients.